Time remaining:
5. Please check my answer to make sure it is correct. Thanks!

label Algebra
account_circle Unassigned
schedule 0 Hours
account_balance_wallet $5

Apr 27th, 2015

we have f(x)=(-5x+2)/(x+5) 

so we take :  x=(-5y+2)/(y-5) so : x(y-5) = -5y+2   so : xy - 5x = -5y + 2  so : xy + 5y =  5x + 2 

so :  y(x+5)=5x + 2 ====>>>  y = (5x + 2)/(x + 5)  so : f^-1(x) = (5x + 2)/(x + 5 )

Good Luck 

Apr 26th, 2015

So my answer was right then?

Apr 26th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Apr 27th, 2015
...
Apr 27th, 2015
Sep 21st, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer